Aspek Makroekonomi dan Pengaruhnya terhadap Kapitalisasi Saham ISSI Periode 2016-2023 - Nurul Annisya; Sri Astuty; Irwandi Irwandi (CV. ULIL ALBAB CORP, 2025)
This study explores the inequality of the potential of the Muslim population in Indonesia that is not realized properly in the amount of capitalization of the ISSI Sharia Capital Market using macroeconomic variables of BI Rate interest rates, Money Supply and Rupiah Exchange Rates for the 2016-2023 Period with the Vector Error Correction Model (VECM) analysis method. The population in this study is the ISSI market capitalization with a total of 384 observations of data with a data collection technique, namely Purposive Sampling from the total amount of capitalization of companies listed on the ISSI index with the Vector Error Correction Model (VECM) analysis method. The results of this study indicate that in the short term, only the BI Rate interest rate with a t-statistic value of -1.99264 > t-table value of 1.986086317 and the Rupiah exchange rate with a t-statistic value of -2.72958 > t-table of 1.986086317 which means it has a negative influence on ISSI stock capitalization while the Money Supply variable does not have a significant influence on ISSI stock capitalization with a t-statistic value [-1.02110 < t-table of 1.986086317. In the long term, the BI Rate interest rate contributes negatively to the capitalization of ISSI shares while the Money Supply and Rupiah Exchange Rate have a significant positive influence on the capitalization of ISSI shares -3.76772> t-table of 0.26454 and the Rupiah Exchange Rate with a t-statistic value of -3.38406> t-table of 0.26454 which means that the amount of money in circulation and the rupiah exchange rate have a negative influence on the number of investors. In the long term, the BI Rate interest rate contributes negatively to the capitalization of ISSI shares with a t-statistic value of [-2.13166> t-table of 1.986086317 while the Money Supply and Rupiah Exchange Rate have a significant positive influence on the capitalization of ISSI shares with a t-statistic value greater than the t table, respectively with values of 8.72868 and 2.64624